2019
DOI: 10.1159/000501843
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into Weather and Stroke: Influences of Specific Air Masses and Temperature Changes on Stroke Incidence

Abstract: Background/Objectives: Meteorological factors seem to influence stroke incidence, however, the complex association between weather and stroke remains unclear. Possible explanations from the literature do not categorize into subdivisions of ischemic strokes, only have small patient numbers, or refer to a selection of isolated weather elements without investigating weather changes and more. Method: In this exploratory trial, almost 18,000 stroke cases from a single stroke center in Southern Germany were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…From the results obtained, the atmospheric factors that predict HS with highest accuracy were not absolute values of humidex, WS, AP, and temperature but their monthly changes. These results were consistent with previous statistical analysis (31) and justified the use of a distributed lag nonlinear model in this study. Furthermore, we demonstrated that HS incidence is affected by air masses, i.e.…”
Section: Effect Of Clinicodemographic Risk Factors and Weather Parame...supporting
confidence: 93%
See 2 more Smart Citations
“…From the results obtained, the atmospheric factors that predict HS with highest accuracy were not absolute values of humidex, WS, AP, and temperature but their monthly changes. These results were consistent with previous statistical analysis (31) and justified the use of a distributed lag nonlinear model in this study. Furthermore, we demonstrated that HS incidence is affected by air masses, i.e.…”
Section: Effect Of Clinicodemographic Risk Factors and Weather Parame...supporting
confidence: 93%
“…Exposure to cold temperatures can disrupt normal homeostatic mechanisms and increase heart rate, blood pressure, platelet count, blood viscosity, serum low-density lipoprotein-cholesterol concentration, and other cardiac biomarkers, thereby elevating cardiovascular event risk (37,38). We showed the adverse effect of low temperatures on ICH incidence, which is consistent with the findings of several previous studies (18,20,31,39,40,41,42,43). However, lower or unchanged HS risk was also reported (44).…”
Section: Association Of Hs Incidence With Weathersupporting
confidence: 90%
See 1 more Smart Citation
“…Most of these regions are characterized by hot summers, and many authors associate IS risk with hot weather. 2,5,47,48 However, in other regions with hot summers, but without strong seasonal fluctuations in atmospheric pressure, for example, in Italy, Croatia and Greece, IS were more common in winter than in summer. 19,22,25,30,34 Also, studies in Novosibirsk have shown an increase in IS in winter.…”
Section: Discussionmentioning
confidence: 99%
“…A later study justified an effect of age, sex, and smoking status on the IS morbidity [34]. Some scientists analysed changes in the air masses due to the wind and justified that dry polar air was associated with a lower IS risk [35]. Further studies are required to get an insight if the weather parameters interact with individual risk factors to influence the IS incidence in distinct geographic locations.…”
Section: Introductionmentioning
confidence: 99%